The Ability of Independent Farmers to Meet the Needs of Life during Replanting - Burhan, Djono Albar; Apriyanto, Mulono; Azhar, Ali; Fikri, KMS Novyar Satriawan; Yulianti, Yulianti (Akademi Komunitas Perkebunan Yogyakarta, 2026)
The cultivation of oil palm has enhanced welfare and food security for economically disadvantaged families in Indonesia. In Riau Province, the majority of farms are owned by independent smallholders. The land area with old or damaged crops constitutes 43.38% of the total area. Smallholders must undertake replanting to prevent a decline in productivity and income. The research aims are: 1) to describe oil palm replanting in the Tapung Sub-District of Kampar Regency, and 2) to analyze the revenue of smallholders. 3) Forecasting the impact of smallholder income on home living expenses during the replanting phase. This research was conducted using descriptive and quantitative methods. The findings indicated a replanting area of 1.96 hectares for the oil palm field. Before replanting, the income from palm oil farming was IDR 4,229,530 per month. Following replanting, when crops had failed to produce, smallholders' revenue amounted to IDR 1,239,486 per month derived from the cultivation of food crops, specifically maize, chile, and peanuts.The monthly household expenses amount to IDR 2,613,542, with income from horticultural or food plant cultivation contributing 47.42 percent. It signifies the usage of palm coil upright land prior to agricultural yield as a policy under scrutiny for its impact on household income.